Purine Nucleotides in the Regulation of Brown Adipose Tissue Activity - Bast-Habersbrunner, Andrea; Fromme, Tobias (Frontiers in Endocrinology, 2020)
Non-shivering thermogenesis in mammalian brown adipose tissue is a powerful mechanism to defend normothermia in cold climates. To minimize the loss of chemical energy, the central functional component, mitochondrial uncoupling protein 1, UCP1, must be tightly regulated. The canonical pathway of UCP1 activation includes lipolytic release of free fatty acids in response to an adrenergic signal. Activating fatty acids overcome constitutive inhibition of UCP1 by the di- and triphosphate forms of purine nucleotides, i.e. ATP, ADP, GTP and GDP. Cellular concentrations of inhibitory, free nucleotides are subject to significant, adrenergically induced alterations. The regulatory components involved may constitute novel drug targets to manipulate brown fat thermogenesis and thereby organismic energy balance. We here review evidence for and against a dominant role of nucleotides in thermogenic control, describe conceptual routes to endogenously and pharmacologically alter free nucleotide pool size, speculate on a signaling role of degradation products released from active brown fat, and highlight gaps in our understanding of signaling and metabolic pathways involved.